Assessment of the Shear Bond Strength between Nanofilled Composite Bonded to Glass-ionomer Cement Using Self-etch Adhesive with Different pHs and Total-Etch Adhesive - Sharafeddin, Farahnaz (J Dent (Shiraz), 2016)
STATEMENT OF THE PROBLEM: In the sandwich technique, the undesirable bond between the composite resin and glass-ionomer cement (GIc) is one of the most important factors which lead to the failure of restoration. Total-etch and self-etch adhesives may improve the bond strength based on their pH. PURPOSE: The purpose of this study was to evaluate the shear bond strength between the nanofilled composite resin and GIc using different adhesives. MATERIALS AND METHOD: In this experimental study, 40 specimens (6×6mm) in 4 groups (n=10) were prepared in acrylic mold. Each specimen contained conventional GI ChemFil Superior with a height of 3mm, bonded to Z350 composite resin with a height measured 3mm. In order to bond the composite to the GI, the following adhesives were used, respectively: A: mild Clearfil SE Bond self-etch (pH=2), B: intermediate OptiBond self-etch (pH=1.4), C: strong Adper Prompt L-Pop (pH=1), and D: Adper Single Bond 2 total-etch (pH=7.2). The shear bond strength was measured by using universal testing machine with a crosshead speed of 1mm/min. One-way ANOVA and Tukey’s test were used to analyze the data (p< 0.05). RESULTS: The shear bond strength in group A was significantly higher than group B (p= 0.002), C (p< 0.001), and D (p< 0.001). Moreover, the shear bond strength of groups A and B (self-etch) was significantly different from group D (total-etch) (p< 0.001); and C (self-etch) with D (p= 0.024). CONCLUSION: The results of this study showed that applying the mild self-etch adhesive between the composite and the GIc results in stronger shear bond strength compared to intermediate and strong self-etch adhesives. Moreover, the self-etch adhesive increased the shear bond strength between composite resin and GIc more significantly than total-etch adhesive.